Ethnobotanical study of medicinal plants among the Karo Tribe in Kuala Sub-district, Langkat District, North Sumatra, Indonesia - ABDUL RASYID FAKHRUN GANI; UTAMI SRI HASTUTI; SULISETIJONO SULISETIJONO; FRIDA KUNTI SETIOWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Gani ARF, Hastuti US, Sulisetijono S, Setiowati FK. 2024. Ethnobotanical study of medicinal plants among the Karo tribe in Kuala Sub-district, Langkat District, Indonesia. Biodiversitas 25: 2960-2968. Indonesia has a high diversity of plants. One area of Indonesia with a high diversity of plants is Kuala Sub-district, Langkat District, North Sumatra Province, Indonesia. The Karo tribe inhabits Kuala Sub-district, and they still apply the ethnomedicine knowledge in their life; this study aims to: (i) document ethnomedicine knowledge of the use of medicinal plants in Kuala Sub-district, (ii) Analyze the use value and cultural significance index to determine the level of use of medicinal plants by the Karo people in Kuala Sub-district. Ethnomedicine data were collected for eleven months, from October 2022 to April 2024. The data sources in this research were 205 informants (25 key informants and 180 additional informants). Data from 25 key informants was used to determine the cultural significance index, while data from 180 additional informants was used to determine use value (UV). ICS data was collected by conducting focus group discussions with key informants, while UV data collection was carried out using survey techniques. The research was conducted through semi-structured interviews to determine various medicinal plants' quality, intensity, and exclusivity. This research shows 49 plants used in medicinal practice, and the highest significant cultural index and use value is Kaempferia galanga. The part of the plant that is most widely used is the leaf. The most common disease experienced by the Karo people in Kuala Sub-district is flatulence and many medicinal plants are used to treat this disease.